Hubungan antara Kinerja Kader dengan Partisipasi Peserta dalam Kegiatan Posyandu di Pukesmas Nagari Sungai Tunu Utara Kecamatan Ranah Pesisir - Pendi Saputra; Solfema Solfema; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research was motivated by the low participation of participants in posyandu activities, the authors suspect this was due to a lack of cadre performance in carrying out and running all the hybrid five posyandu. The objectives of this study were (1) to describe the performance of cadres in posyandu activities (2) to describe the participation of participants in posyandu activities (3) to see the relationship between cadre performance in posyandu activities and participation of participants. This research includes correlational research. The population of this study is mothers have children who are included in the age group of toddlers in the posyandu, amounting to 35 people. Data collection techniques used in this study are questionnaires, while the data collection tool used is a quensioner. The research variable is the performance of cadres (variavel X) and participant participation (variable Y), then the data is processed using a percentage formula to see the picture and product moment formula to see the relationship between the two variables. The results of the research show that (1) cadre performance in posyandu activities is poor (2) participant participation in health service posyandu activities is low (3) there is a relationship between cadre performance and participation in posyandu activities in the pukesmas Nagari Sungai Tunu Utara. Suggestions for researching are: to posyandu cadres to improve cadre performance in carrying out posyandu activities.Keywords: Cadre Performance, Participant Participation, Posyandu Activities